Strengthening Indonesia’s Millennial Generation Organizational Commitment and Loyalty: The Role of Religiosity - Hunik Sri Runing Sawitri; Muhammad Abdullah ‘Azzam (The Eastasouth Management and Business, 2023)
The millennial generation is the key to Indonesia's future success, but there are still profound misunderstandings, especially regarding the millennial generation's organizational commitment and loyalty. Rather than focusing on these misunderstandings, this article invites researchers especially on Indonesia's generational cohort to look up another factor to strengthen the millennial generation's organizational commitment and loyalty, and one of those factors is religiosity. This article provided a grounded theory approach by providing an in-depth analysis of several topics especially organizational commitment and religiosity among the Indonesia millennial generation. This in-depth analysis resulted in three conceptual proposals, that proposed how religiosity as a variable could be utilized, in organizational commitment and loyalty study among the millennial generation. These proposals could help future researchers create a basis for theoretical development or conduct ab empirical research on this subject.